Effect of Alkylsilyl Side‐Chain Structure on Photovoltaic Properties of Conjugated Polymer Donors. Issue 8 (4th December 2017) - Bin, Haijun; Yang, Yankang; Peng, Zhengxing; Ye, Long; Yao, Jia; Zhong, Lian; Sun, Chenkai; Gao, Liang; Huang, He; Li, Xiaojun; Qiu, Beibei; Xue, Lingwei; et al.
Abstract: Side‐chain engineering is an important strategy for optimizing photovoltaic properties of organic photovoltaic materials. In this work, the effect of alkylsilyl side‐chain structure on the photovoltaic properties of medium bandgap conjugated polymer donors is studied by synthesizing four new polymersJ70, J72, J73, andJ74 on the basis of highly efficient polymer donorJ71 by changing alkyl substituents of the alkylsilyl side chains of the polymers. And the photovoltaic properties of the five polymers are studied by fabricating polymer solar cells (PSCs) with the polymers as donor and an n‐type organic semiconductor (n‐OS) m ‐ITIC as acceptor. It is found that the shorter and linear alkylsilyl side chain could afford ordered molecular packing, stronger absorption coefficient, higher charge carrier mobility, thus results in higher J sc and fill factor values in the corresponding PSCs. While the polymers with longer or branched alkyl substituents in the trialkylsilyl group show lower‐lying highest occupied molecular orbital energy levels which leads to higher V oc of the PSCs. The PSCs based onJ70 : m ‐ITIC andJ71 : m ‐ITIC achieve power conversion efficiency (PCE) of 11.62 and 12.05%, respectively, which are among the top values of the PSCs reported in the literatures so far. Abstract : Side‐chain engineering is performed to optimize photovoltaic properties of the 2D‐conjugated polymer donors. The polymer solar cells with m ‐ITIC as acceptor andJ70 andJ71 polymer donors with shorter and linear alkyl substituents in their alkylsilyl side chains achieve power conversion efficiency of 11.62% and 12.05%, respectively.